3D ultrasound file reading and coordinate transformations - Looney, Pádraig T. (J Open Source Softw, 2019)
The Kretzfile format is used to store 3D ultrasound data, from GE Voluson ultrasound scanners. The geometry used in these hies is a toroidal coordinate system. Cartesian coordinates are required to allow application of advanced image libraries like ITK and scikit-image. We present ITK transformation and utilities to convert Kretzfiles to cartesian coordinates. Previous work (SlicerHeart, 2017) has enabled the reading of kretz files and approximate coordinate transformations. This work will enable medical imaging researchers to investigate clinically 3D ultrasound.